Religiusitas Generasi Milenial: Kajian Fenomenologis terhadap Gerakan Hijrah di Kota Bandung - Goffary, Irfan (International Journal of Nusantara Islam, 2024)
The hijrah phenomenon has become part of the religious dynamics of contemporary society, especially among urban youth. The hijrah Youth Movement, known for its popular approach to preaching, combines religious values with popular culture and utilizes digital technology as a medium for preaching. This study aims to analyze the phenomenon of hijrah as a social construction using Berger's theory, which includes externalization, objectivation, and internalization. The research method used was descriptive qualitative, with a sociological approach and phenomenological analysis. The results showed that the hijrah movement developed as a response to social change and modernity and became a new religious identity for the millennial Muslim generation.  hijrah is not only understood as an individual spiritual transformation, but also as a collective social phenomenon that forms new patterns in religious practice. In addition, social media plays an important role in the spread of this movement, creating increasingly massive digital activism. However, the massiveness of the hijrah movement in cyberspace raises challenges to the deep understanding of the history and essence of the hijrah itself. Therefore, it is necessary to integrate the study of hijrah history into religious education to avoid distortion of meaning. Further research is needed to review the impact of this movement from a futurological perspective, especially in the face of an era of artificial intelligence that could affect future religious trends.